2020
DOI: 10.1021/acsbiomaterials.0c00091
|View full text |Cite
|
Sign up to set email alerts
|

Electro-mechanical and Polarization-Induced Antibacterial Response of 45S5 Bioglass–Sodium Potassium Niobate Piezoelectric Ceramic Composites

Abstract: Besides the excellent osteoconductivity and biocompatibility of 45S5 bioglass (BG), poor mechanical and electrical properties as well as susceptibility toward bacterial adhesion limit its widespread clinical applications. In this context, the present study investigates the effect of addition of piezo­electric sodium potassium niobate (Na0.5K0.5NbO3; NKN) on mechanical, dielectric, and antibacterial response of BG. BG–xNKN (x = 0, 10, 20, and 30 vol%) composites were synthesized at 800 °C for 30 min. The phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…The quantitative analysis, i.e., bacterial viability, was measured using MTT assay. The samples were cultured in 24 well tissue culture plates with an equal amount of bacterial cells (200 μL per well with 0.1 OD, i.e., optical density).The detailed procedure is reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The quantitative analysis, i.e., bacterial viability, was measured using MTT assay. The samples were cultured in 24 well tissue culture plates with an equal amount of bacterial cells (200 μL per well with 0.1 OD, i.e., optical density).The detailed procedure is reported elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…Few studies reported the effect of charge induced by the polarization on the biological effect of NKN. , It has been suggested that the formation of new bones is influenced by the piezoelectric behavior of the implant material . The negatively charged surfaces promote the osteoblast cell activity .…”
Section: Introductionmentioning
confidence: 99%
“…Electroactive nanomaterials are generally divided into two categories: conductive nanomaterials and nonconductive nanomaterials. Piezoelectric nanomaterials belong to the category of nonconductive nanomaterials and are widely used in many fields such as antimicrobial, [ 23,24 ] tumor treatment, [ 25 ] and biosensing. [ 26,27 ] Interestingly, traces of naturally occurring piezoelectric materials can be found in components of the human body such as bones, skin, amino acids, and proteins.…”
Section: Introductionmentioning
confidence: 99%
“…in many fields such as antimicrobial, [23,24] tumor treatment, [25] and biosensing. [26,27] Interestingly, traces of naturally occurring piezoelectric materials can be found in components of the human body such as bones, skin, amino acids, and proteins.…”
mentioning
confidence: 99%
“…[5][6][7] Therefore, the development of polarizable prosthetic implants has attracted significant attention in recent years. 1,2,4,[8][9][10][11][12][13][14] In orthopedic implants, the predominant portion (65%) of bacterial infections is attributed to gram-positive (GP) bacteria, especially, Staphylococcus epidermidis and Staphylococcus aureus. However, gramnegative (GN) bacteria, for example, Escherichia coli and Pseudomonas aeruginosa are responsible for approximately 11% of total bacterial infections in orthopedic implants.…”
Section: Introductionmentioning
confidence: 99%